Efektivitas terapi perilaku kognitif untuk terapi depresi pada mahasiswa keperawatan - Galih Jatnika; Asep Badrujamaludin; Ismafiaty Ismafiaty (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Depression includes disturbances in thought processes and content characterized by feelings of sadness, loss of hope and loss of interest in almost all activities. Depression is the most frequent cause of mental health disorders and the highest cause of disability in the population in Indonesia for the last 3 decades. Depression is more common at the age of 15-24 years or in the range of adolescents with an incidence rate of 6.2% and experienced a seven-fold increase during the Covid-19 pandemic situation, that can lead stressful situations for students which can result a depressive disorders. Efforts are needed to reconstruct negative thoughts into positive thoughts through cognitive behavior therapy.Purpose: To identify the effectiveness of cognitive behavior therapy for depression during the Covid-19 pandemic among nursing students.Method: A pre-experimental with one group pre-test and post-test. Respondents in this study were 20 students of the Unjani Fitkes Bachelor of Nursing study program. Respondents were given cognitive behavior therapy interventions in 3 sessions for 3 weeks. To ensure that there was a decrease in depressive symptoms, depression was measured using the Beck Depression index (BDI) before and after the intervention. Furthermore, the research data was analyzed using the dependent t test.Results: The average depression before being given an intervention was 26.25, while the average depression after being given cognitive behavioral therapy was 34.65.Conclusion: Cognitive behavioral therapy is one of the intervention options in reducing depression, although the results in this study were not proven to be effective in reducing depression in nursing students at Fitkes Unjani.Keywords: Cognitive Behavioral Therapy; Depression; Nursing StudentPendahuluan: Depresi termasuk gangguan proses dan isi pikir yang ditandai dengan rasa kesedihan, kehilangan harapan dan kehilangan minat di hampir semua aktivitas. Depresi merupakan penyebab paling sering gangguan kesehatan mental dan penyebab disabilitas tertinggi pada penduduk di Indonesia selama 3 dekade terakhir. Depresi lebih sering terjadi pada usia 15 – 24 tahun atau pada rentang remaja dengan angka kejadian sebesar 6.2 % dan mengalami peningkatan tujuh kali lipat selama pandemi Covid-19 yang bisa berdampak adanya situasi stress full bagi mahasiswa yang memperberat atau menimbulkan gangguan depresi pada mahasiswa keperawatan. Diperlukan upaya untuk merekonstruksi dari pikiran negatif menjadi pikiran positif melalui cognitive behavior therapy.Tujuan: Untuk mengidentifikasi efektivitas cognitive behavior therapy terhadap depresi di dalam kondisi pandemi Covid-19 pada mahasiswa Fitkes Unjani.Metode: Pre eksperimen dengan one group pre-test and post-test. Responden pada penelitian ini merupakan mahasiswa prodi ilmu keperawatan S1 Fitkes Unjani sebanyak 20 responden. Responden diberikan intervensi cognitive behavior therapy sebanyak III sesi selama 3 minggu. Untuk memastikan adanya penurunan gejala depresi dilakukan pengukuran depresi menggunakan Beck Depression index (BDI) pada saat sebelum dan sesudah pemberian intervensi.Selanjutnya data penelitian dilakukan analisis menggunakan uji t dependen.Hasil: Didapatkan rerata depresi sebelum diberikan intervensi sebesar 26.25 sedangkan rerata depresi setelah diberikan pemberian cognitive behavioral therapy sebesar 34.65.Simpulan: Cognitive behavioral therapy menjadi salah satu pilihan intervensi dalam menurunkan depresi walaupun hasil dalam penelitian ini tidak terbukti secara efektif dapat menurunkan depresi pada mahasiswa keperawatan Fitkes Unjani.